2012
DOI: 10.1021/jp300578h
|View full text |Cite
|
Sign up to set email alerts
|

Atomic and Electronic Processes during the Formation of an Ionic NaCl Monolayer on a Covalent Si(100) Surface

Abstract: An atomic layer of stoichiometric NaCl was formed on a covalent Si(100) surface after two successive half-reactions at room temperature. The first half-reaction due to Cl 2 exposure generates a square array of Cl adatoms with a distance close to that in a NaCl(100) surface plane. By utilizing scanning tunneling microscopy (STM), corelevel photoemission spectroscopy, and ab initio density functional theory (DFT) calculations, it was found that progressive deposition of Na in the second-half reaction results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
(105 reference statements)
1
6
0
Order By: Relevance
“…The p(2 × 2) and c(4 × 2) structures consisting of alternating dimers are seen in the STM images and the intrinsic properties of the clean Si(100) become quite complex [29,30]. As reported elsewhere [31], our calculations showed that the buckled phase is favored by 0.08 eV per (1 × 1) supercell over the symmetric (2 × 1) phase and that other structure parameters are consistent with previous findings [26,28,32].…”
Section: Resultssupporting
confidence: 91%
“…The p(2 × 2) and c(4 × 2) structures consisting of alternating dimers are seen in the STM images and the intrinsic properties of the clean Si(100) become quite complex [29,30]. As reported elsewhere [31], our calculations showed that the buckled phase is favored by 0.08 eV per (1 × 1) supercell over the symmetric (2 × 1) phase and that other structure parameters are consistent with previous findings [26,28,32].…”
Section: Resultssupporting
confidence: 91%
“…The atomic-scale imaging of the metal-supported insulating layers in scanning tunneling microscopy (STM) is also possible, due to mixing of electronic states of the metal and insulating film for thicknesses 1 nm. A suitable dielectric material for molecular nanoscience purposes is NaCl [1,2,4,7,8], whose popularity is based on its ease of thin film deposition by vacuum sublimation of NaCl molecules from solid sodium chloride, and on the formation of well-defined one to three monolayer (ML) thick islands on low-index surfaces of noble [9][10][11][12][13] and simple metals [14], and semiconductors [15]. The NaCl layers grow in (100) orientation irrespective of the substrate orientation, and this is indicative of a weak overlayer-substrate coupling.…”
mentioning
confidence: 99%
“…A in [001] direction and 3:83 AE 0:05 A in [110] direction to be compared with values of 3.96 Å for bulk NaCl and 3.56 Å for a free ML [15] (the interaction with the surface counteracts the shrinking due to reduced dimensionality [25]); this yields a [ð3=2Þ a½110 Â ð11=10Þ a½001 ] overlayer lattice in terms of the Cu(110) unit cell vectors. In Fig.…”
mentioning
confidence: 99%
“…This was previously observed by Chung et al upon deposition of NaCl on Si(100), with a chemical shift of +0.9 eV for Si-Cl species relative to the bulk Si 2p 3/2 peak. 20,21 Matsuo et al studied the surface reaction of molecular and atomic chlorine on Si(100) and Si(111) and found not only Si-Cl by exposure to molecular chlorine but also Si-Cl x (x = 2-4) by exposure to atomic chlorine. 22 They reported Si-Cl at a binding energy of 100.5 eV and an additional chemical shift of +1 eV for every additional chlorine bond.…”
Section: The Si 2p Core Levelmentioning
confidence: 99%